Changes in the Prevalence of Embryologic Remnants in Umbilical Cord With Gestational Age. (July 2019) - Grottling, Emma; Gisselsson, David
The aim of this study was to examine the prevalence of embryologic remnants in umbilical cords of different gestational ages. Sections from 392 umbilical cords were examined using light microscopy. Of these, 52% contained at least 1 remnant, most commonly of the allantoic duct type. Although there was a significant decrease in vitelline duct remnants over increasing gestational age, from 11% at weeks 11–25 to 1.6% at weeks 36–42 ( P = .009; χ 2 test), the allantoic duct remnants remained constant in prevalence irrespective of gestational age.